1997
DOI: 10.1038/ki.1997.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose and pyruvate in acidic and non-acidic peritoneal dialysis fluids on leukocytes cell functions

Abstract: A new peritoneal dialysate containing pyruvate anions has been tested for its effects on cell functions and compared with conventional lactate and bicarbonate based solutions. The dialysate has a final pH of 5.4 to 5.6 and is composed of 1.36 to 3.86% glucose-monohydrate, 132 mmol/liter sodium, 1.75 mmol/liter calcium, 0.75 mmol/liter magnesium, 102 mmol/liter chloride and 35 mmol/liter pyruvate. For cytotoxicity testing peritoneal macrophages and peripheral blood mononuclear cells (PBMC) were exposed to conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
1
18
1
4
Order By: Relevance
“…As quoted above, another important step in the formation or use of pyruvate is catalysed by rapid and reversible transamination reactions, for example catalysed via alanine transaminase, producing α-ketoglutarate and alanine (Cicalese et al 1996a, 1996b; Edlund and Halestrap 1988; Gardner and Leese 1988; Selvaraj and Sbarra 1966; Wiemer et al 1995). For leukocytes this is of major importance, because α-ketoglutarate, converted from pyruvate in particular, is responsible for key metabolic and synthetic roles which are essential in cellular viability (Curi et al 1988; Gabbianelli et al 2007; Mahiout et al 1997; Miwa et al 2000; Ramakrishnan et al 1998; Zhou and Yu 1998) and can be very rapidly into a precursor of numerous amino acids, synthetic metabolic intermediates as well as macromolecular synthesis (Curi et al 1989, 1988; Fuchs et al 1994; Riedel et al 1992; Serrano and Curi 1989; Venizelos and Hagenfeldt 1985). Interesting findings suggest indeed that α-ketoglutarate, which is also one of the most important intracellular nitrogen transporters, is not only a key intermediate in the TCA cycle (coming after isocitrate and before succinyl CoA) but also can replenish the cycle in anaplerotic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…As quoted above, another important step in the formation or use of pyruvate is catalysed by rapid and reversible transamination reactions, for example catalysed via alanine transaminase, producing α-ketoglutarate and alanine (Cicalese et al 1996a, 1996b; Edlund and Halestrap 1988; Gardner and Leese 1988; Selvaraj and Sbarra 1966; Wiemer et al 1995). For leukocytes this is of major importance, because α-ketoglutarate, converted from pyruvate in particular, is responsible for key metabolic and synthetic roles which are essential in cellular viability (Curi et al 1988; Gabbianelli et al 2007; Mahiout et al 1997; Miwa et al 2000; Ramakrishnan et al 1998; Zhou and Yu 1998) and can be very rapidly into a precursor of numerous amino acids, synthetic metabolic intermediates as well as macromolecular synthesis (Curi et al 1989, 1988; Fuchs et al 1994; Riedel et al 1992; Serrano and Curi 1989; Venizelos and Hagenfeldt 1985). Interesting findings suggest indeed that α-ketoglutarate, which is also one of the most important intracellular nitrogen transporters, is not only a key intermediate in the TCA cycle (coming after isocitrate and before succinyl CoA) but also can replenish the cycle in anaplerotic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…It may be associated with the maintenance of intracellular pH close to physiological, due to its low buffering capacity, improvement of cellular glucose metabolic pathways and redox state [38,39,40], and sustainment of intracellular calcium homeostasis in high glucose concentrations. Mahiout et al [41] speculated that when pyruvate is used in the dialysate, the glucose-induced respiratory inhibition (Crabtree effect) is reduced. But Zhou [40 ]argues that exogenous pyruvate in PDS could not be an energy source for cells and also the Crabtree effect might not occur in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro suppressive effects of hyperosmolarity [4, 8, 13], high lactate concentrations [14,15,16], GDPs [6, 17, 18] and acidity [19] on various leukocyte functions are well known. In our previous study, we confirmed the importance of high lactate concentrations, GDPs and hyperosmolarity in the inhibition of leukocyte recruitment in vivo [7].…”
Section: Discussionmentioning
confidence: 99%